Charge-balanced terpolymer poly(diethylaminoethyl methacrylate-hydroxyethyl methacrylate-2-acrylamido-2-methyl-propanesulfonic acid) hydrogels and cryogels: scaling parameters and correlation with composition. Issue 46 (16th October 2020) - Okten Besli, Nur Sena; Orakdogen, Nermin
Abstract : Scaling parameters relating the preparation conditions to the swelling degree, reduced modulus and effective crosslinking density of poly(diethylaminoethyl methacrylate- co -hydroxyethyl methacrylate- co -2-acrylamido-2-methyl-propanesulfonic acid) gels. Abstract : The scaling laws relating the preparation conditions to the swelling degree, reduced modulus and effective crosslinking density of poly(diethylaminoethyl methacrylate- co -hydroxyethyl methacrylate- co -2-acrylamido-2-methyl-propanesulfonic acid), henceforth designated as PDHA, gels prepared by radical crosslinking copolymerization in a solvent mixture were reported. Charge-balanced terpolymer PDHA hydrogels and cryogels (PDHA-Hgs and Cgs) were prepared in different monomer feed compositions. The swelling dependence of the reduced modulus was described by a power law relationship G r ≈ ( φ V ) m with an exponent of m = −0.30 at low swelling degree, while in the high swelling region the scaling becomes 0.21, indicating the finite extensibility of the network chains. The scaling exponent for the swelling degree and terpolymer composition, φ V ≈ ( Nν 02) m, was found to be −0.13, indicating the increasing extent of the topological constraints arising from the trapped entanglements. By combining elasticity and swelling results, the scaling relationship between the apparent crosslink density and HEMA content used in the terpolymer feed was obtained as a cubic polynomial of the mol% of HEMA. In the HEMA-rich terpolymer PDHA Hgs and Cgs, the swelling degree was possibly controlled by the HEMA part of the terpolymer network, while the presence of DEAEM units in the network triggered the thermoresponsive swelling behavior. The dependence of interaction parameter χ on the volume fraction of the crosslinked terpolymer network in the swollen gel ν 2 was evaluated and the results revealed extremely strong concentration dependence of χ for all terpolymer samples. Because of their inherent properties, the resulting terpolymer gels might contribute to the improvement of the loading capacity of polymers used in anticancer drug delivery systems.